Lithium salt composite material, negative electrode sheet and preparation method thereof, battery and electrical device

By using lithium salt composite materials in the negative electrode sheet, the problem of active lithium consumption caused by rupture of the SEI film of the prelithiated negative electrode sheet is solved, and the efficient circulation and stable performance of the battery are achieved.

CN115842118BActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211430472.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2025-03-07
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

The existing prelithiated negative electrode sheets are prone to rupture during the battery cycle, resulting in the continuous consumption of active lithium and reducing the battery cycle performance.

Method used

Lithium salt composite materials, including lithium salt particles and metal lithium clad layers coated with lithium salt particles, are used as additives for the negative electrode sheet. During the charging and discharging process, the lithium salt composite material provides lithium ions, replenishes lithium, and forms a local high-concentration electrolyte in the negative electrode active layer to form a stable and rich SEI film.

Benefits of technology

It improves the first-effect and cycling performance of the battery, enhances the stability and ion conductivity of the SEI film, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115842118B_ABST
    Figure CN115842118B_ABST
Patent Text Reader

Abstract

The present application discloses a lithium salt composite material, a negative electrode sheet and a preparation method thereof, a battery and an electrical device. The lithium salt composite material (10) of the present application contains lithium salt particles (11) and a metal lithium coating layer (12) coating the lithium salt particles (11). The negative electrode active layer (20) of the negative electrode sheet of the present application contains the lithium salt composite material (10). The battery of the present application contains the negative electrode sheet of the present application. After the lithium salt composite material of the present application is added to the negative electrode sheet as an additive, it can play a role in replenishing lithium and improving the cycle performance of the battery. The negative electrode sheet of the present application can improve the initial efficiency and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium salt composite material, a negative electrode sheet and a preparation method thereof, a battery and an electrical device. Background Art

[0002] Energy conservation and emission reduction are the key to the sustainable development of the automobile industry. Electric vehicles have become an important part of the sustainable development of the automobile industry due to their advantages in energy conservation and environmental protection. For electric vehicles, battery technology is an important factor in their development.

[0003] Moreover, as battery applications become more and more popular, the market has increasingly higher requirements for battery-related performance, such as cycle performance.

[0004] However, during the first charge and discharge process of lithium-ion batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a layer of "solid electrolyte interface" (SEI) covering the surface of the electrode material. The formation of the SEI film will cause the loss of active lithium in the positive electrode material. In this way, part of the lithium in the first discharge cannot be embedded back into the positive electrode material, resulting in a decrease in the initial efficiency.

[0005] In order to reduce or make up for the lithium ions consumed by the SEI film, one of the currently disclosed effective methods is to perform pre-lithiation treatment on the surface of the negative electrode plate to form a lithium compound layer on the surface of the active layer of the negative electrode plate. However, studies have found that the SEI film of the pre-lithiation negative electrode plate is prone to rupture during the battery cycle, and a new SEI film is formed at the rupture of the SEI film, resulting in continuous consumption of active lithium. This process reduces the battery cycle performance. Summary of the invention

[0006] In view of the above problems, the embodiments of the present application provide a lithium salt composite material, a negative electrode sheet and a preparation method thereof, a battery and an electrical device to solve the technical problem that the existing pre-lithiation negative electrode continuously consumes active lithium during the cycle, resulting in low battery cycle performance.

[0007] In a first aspect, the present invention provides a lithium salt composite material, which includes lithium salt particles and a metal lithium coating layer coating the lithium salt particles.

[0008] The lithium salt composite material of the embodiment of the present application uses lithium salt coated with metallic lithium. When the lithium salt composite material of the embodiment of the present application is added to the negative electrode sheet as an additive, it can provide lithium ions during the charge and discharge process, play a role in lithium replenishment, and improve the initial efficiency of the battery; and after contacting with the electrolyte, the lithium salt particles can form a local high-concentration electrolyte in the negative electrode active layer, thereby forming a stable and component-rich SEI film, thereby improving the cycle performance of the negative electrode sheet.

[0009] In some embodiments, the mass ratio of the lithium salt particles to the metal lithium coating layer is 0.05:1 to 1:1.

[0010] In some embodiments, the average particle size Dv50 of the lithium salt composite material is 50 nm to 100 μm.

[0011] By controlling the mass ratio of the metal lithium coating layer and the lithium salt particles and controlling the particle size of the lithium salt composite material, the lithium salt composite material can enhance the first-time efficiency of the battery, improve the stability of the lithium salt concentration contained in the locally high-concentration electrolyte formed in the negative electrode active layer, and improve the stability and ion conductivity of the SEI film.

[0012] In some embodiments, the average particle size Dv50 of the lithium salt particles is 10-500 nm.

[0013] In an exemplary embodiment, the lithium salt in the lithium salt particles includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide) and lithium bis(trifluoromethylsulfonyl imide).

[0014] Lithium salts of these types and particle sizes have good solubility and can form a local high-concentration electrolyte in the negative electrode active layer, thereby improving the stability and ion conductivity of the SEI film.

[0015] In the second aspect, the present application provides a method for preparing a lithium salt composite material. The present application implements a method for preparing a lithium salt composite material comprising the following steps:

[0016] The metallic lithium raw material is used in a dry method to form a metallic lithium coating layer on the surface of lithium salt particles to coat the lithium salt particles.

[0017] The method for preparing the lithium salt composite material in the embodiment of the present application directly forms a coating layer on the surface of lithium salt particles using metallic lithium raw materials, thereby giving the prepared lithium salt composite material the core-shell structure and function possessed by the lithium salt composite material in the embodiment of the present application.

[0018] In some embodiments, the method of forming a metal lithium coating layer on the surface of lithium salt particles by a dry method using a metal lithium raw material comprises the following steps:

[0019] The metallic lithium raw material and the lithium salt particles are mixed and then heat treated in a protective atmosphere to melt the metallic lithium raw material and form a metallic lithium coating layer on the lithium salt particles;

[0020] or

[0021] The metallic lithium raw material and the lithium salt particles are mixed and then roll-pressed to form a metallic lithium coating layer on the lithium salt particles.

[0022] The dry coating method can effectively form a coating layer on the lithium salt particles using the metallic lithium raw material.

[0023] In a third aspect, the present application provides a negative electrode sheet. The negative electrode sheet of the present application includes a current collector and a negative electrode active layer combined with the current collector, wherein the negative electrode active layer contains the lithium salt composite material of the present application embodiment and the lithium salt composite material prepared by the lithium salt composite material preparation method of the present application embodiment.

[0024] The negative electrode sheet of the present application embodiment can effectively improve the initial efficiency of the battery by adding the lithium salt composite material of the present application embodiment to the negative electrode active layer. After contacting with the electrolyte, the lithium salt particles contained in the lithium salt composite material can form a local high-concentration electrolyte in the negative electrode active layer, thereby forming a stable and component-rich SEI film, thereby improving the cycle performance of the negative electrode sheet, and the ion conductivity of the SEI film is high.

[0025] In some embodiments, the mass ratio of the lithium salt composite material to the negative electrode active material is 0.5:100 to 15:100.

[0026] By controlling the content of the lithium salt composite material in the negative electrode active layer, the initial efficiency of the battery can be improved, the stability of the lithium salt concentration contained in the local high-concentration electrolyte formed in the negative electrode active layer can be improved, and the stability and ion conductivity of the SEI film can be improved.

[0027] In some embodiments, the metal lithium in the metal lithium coating layer contained in the lithium salt composite material is at least partially bound to the surface of the negative electrode active material or / and embedded in the surface layer of the negative electrode active material. After the lithium salt composite material contained in the negative electrode active layer contacts the negative electrode active material, at least part of the metal lithium can be bound to the surface of the negative electrode active material or embedded in the surface layer of the negative electrode active material.

[0028] In some embodiments, the average particle size Dv50 of the negative electrode active material is 3-25 μm. The negative electrode active material in this particle size range has a high compaction density.

[0029] In the exemplary embodiment, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, mesophase carbon microspheres, nanocarbon, elemental silicon, silicon-oxygen compounds, silicon-carbon composites, and silicon-tin alloys. These negative electrode active materials have high metallic lithium embedding capabilities and can improve the stability of metallic lithium embedding contained in the lithium salt composite material.

[0030] In a fourth aspect, the present invention provides a method for preparing a negative electrode sheet. The method for preparing a negative electrode sheet in the present invention comprises the following steps:

[0031] Providing a lithium salt composite material; the lithium salt composite material is the lithium salt composite material of the embodiment of the present application or the lithium salt composite material prepared by the method for preparing the lithium salt composite material of the embodiment of the present application;

[0032] The lithium salt composite material and the negative electrode active material are prepared into a negative electrode slurry;

[0033] The negative electrode slurry is coated on at least one surface of the current collector to obtain a negative electrode sheet.

[0034] The negative electrode sheet preparation method of the embodiment of the present application can effectively prepare the lithium salt composite material and the negative electrode active material into a negative electrode active layer, and can be fully dispersed with the negative electrode active material, so that the lithium salt composite material can fully play the role of lithium replenishment during the charge and discharge process and the lithium salt can form a local high-concentration electrolyte in the negative electrode active layer, thereby forming a stable and component-rich SEI film, thereby improving the cycle performance of the negative electrode sheet.

[0035] In some embodiments, the mass ratio of the lithium salt composite material to the negative electrode active material is 0.5:100 to 15:100. The content of the lithium salt composite material in the negative electrode active layer is controlled to improve the role played by the lithium salt composite material.

[0036] In a fifth aspect, the present invention provides a battery. The battery of the present invention comprises the negative electrode sheet of the present invention or the negative electrode sheet prepared by the negative electrode sheet preparation method of the present invention.

[0037] The battery of the embodiment of the present application has good cycle stability, and high first efficiency and energy density.

[0038] In some embodiments, after the battery is subjected to formation treatment, the negative electrode active layer contains exposed lithium salt particles. After the formation treatment, the presence of lithium salt particles can effectively improve the stability of the local high-concentration electrolyte formed in the negative electrode active layer, thereby improving the stability of the SEI film and improving the cycle performance of the negative electrode sheet.

[0039] In some embodiments, after the battery is subjected to formation treatment, a solid electrolyte interface film is formed on the surface of the negative electrode active material contained in the negative electrode sheet, and the solid electrolyte interface film at least partially covers the negative electrode active material. The solid electrolyte interface film at least covers the negative electrode active material, which can improve the cycle performance of the battery.

[0040] In a sixth aspect, an embodiment of the present application provides an electric device. The electric device of the embodiment of the present application includes a secondary battery of the embodiment of the present application, and the secondary battery is used to provide electric energy.

[0041] The electric device in the embodiment of the present application has a long standby or battery life.

[0042] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0044] Figure 1 This is a schematic diagram of the process for preparing the lithium salt composite material according to an embodiment of the present application;

[0045] Figure 2 This is a schematic diagram of the process of preparing the negative electrode sheet according to the embodiment of the present application;

[0046] Figure 3 This is a schematic structural diagram of an implementation of a battery cell according to an embodiment of the present application;

[0047] Figure 4 for Figure 3 An exploded schematic diagram of the battery cell shown;

[0048] Figure 5 This is a schematic structural diagram of an implementation scheme of a battery module according to an embodiment of the present application;

[0049] Figure 6 This is a schematic structural diagram of an implementation scheme of a battery pack according to an embodiment of the present application;

[0050] Figure 7 for Figure 6 A schematic diagram of the exploded structure of the battery pack shown;

[0051] Figure 8 It is a schematic diagram of an implementation of an electrical device including the battery of an embodiment of the present application as a power source.

[0052] The reference numerals in the specific implementation manner are as follows:

[0053] 10. Lithium salt composite materials;

[0054] 11. lithium salt particles, 12. metal lithium coating layer;

[0055] 20. Negative electrode active layer;

[0056] 21. negative electrode active material, 22. metal lithium embedding layer, 23. SEI film 23, 11', residual lithium salt particles after partial dissolution, 24. binder;

[0057] 30. secondary battery cell, 31. housing, 32. electrode assembly, 33. cover plate;

[0058] 40. Battery Module

[0059] 50. battery pack, 51. box body, 52. lower box body. DETAILED DESCRIPTION

[0060] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0061] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0062] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0063] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0064] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0065] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0066] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0067] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0068] The negative electrode active layer in the embodiment of the present application refers to the active layer contained in the negative electrode sheet, which at least contains a layer structure of negative electrode active material and is combined with a current collector.

[0069] SEI film: The Chinese name is solid electrolyte interface, which refers to the reaction between the electrode material and the electrolyte at the solid-liquid interface during the first charge and discharge process of the battery, forming a passivation layer covering the surface of the electrode material.

[0070] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding, and the performance requirements for battery cycle performance and other performance are also getting higher and higher.

[0071] During the first charge and discharge process of lithium-ion batteries, the electrode materials, especially the negative electrode materials, react with the electrolyte at the solid-liquid interface and form a passivation layer covering the surface of the electrode materials with the active lithium ions in the electrolyte, thereby consuming some of the active lithium ions. This results in a reduction in the content of active lithium ions that can be used to shuttle between the positive and negative electrodes, reducing the initial efficiency of the battery.

[0072] Moreover, the SEI film formed by existing negative electrode sheets, such as the commonly used graphite negative electrode, is unstable and easy to rupture. The main reason is that the SEI film has a high content of organic components and lacks inorganic components, and the inorganic components mainly come from the decomposition of lithium salts in the electrolyte. Therefore, during the battery charging and discharging process, the SEI film ruptures and continuously forms a new SEI film, resulting in continuous consumption of active lithium in the electrolyte, which leads to the continuous deterioration of the battery's cycle performance.

[0073] If the lithium salt concentration is maintained by directly adding lithium salt to the electrolyte, the viscosity of the electrolyte will increase, which is not conducive to lithium ion conduction.

[0074] Although existing public reports have shown that the consumption of active lithium in the first full charge of the battery can be effectively reduced by pre-lithiation of the surface of the negative electrode, that is, a layer of lithium compound film is formed on the surface of the negative electrode in advance, thereby improving the battery's initial efficiency and other performance. For example, in a disclosed pre-lithiation negative electrode, a metal lithium layer is first attached to the surface of the negative electrode active layer, followed by baking, and then a reaction gas is introduced to react, so as to generate an SEI film in situ on the surface of the negative electrode active layer. Therefore, it is achieved by artificially forming an artificial SEI film on the surface of the negative electrode active layer in advance to improve the energy density and long cycle performance of lithium-ion batteries.

[0075] However, the inventors found in their research that the SEI film formed by the existing pre-lithiation electrode has a single component and poor ion conductivity. Compared with the SEI film component naturally formed by battery charging and discharging, the pre-lithiation electrode can improve the initial efficiency, but the SEI film formed is less stable and the battery cycle performance is relatively poor.

[0076] In order to improve the stability of the SEI film to improve the battery cycle performance, the inventors have found that by adding a complex of metal lithium and lithium salt to the negative electrode active layer, the metal lithium can be combined with the negative electrode active material or further embedded in the negative electrode active material to play a role in continuous lithium replenishment. After the chemical formation treatment, at least part of the lithium salt can be dissolved in the electrolyte between the negative electrode active material layers to form a local high-concentration electrolyte. The local high-concentration electrolyte forms an inorganic-rich SEI film on the surface of the negative electrode active material, thereby significantly improving the stability of the SEI film and significantly improving the battery cycle performance. Therefore, the following technical solution is proposed.

[0077] Lithium salt composite materials

[0078] In a first aspect, the present application provides a lithium salt composite material. As an embodiment of the present application, the structure of the lithium salt composite material in the present application is as follows Figure 1 As shown in FIG. B , the lithium salt composite material 10 includes lithium salt particles 11 and a metal lithium coating layer 12 coating the lithium salt particles 11 .

[0079] The lithium salt particles 11 contained in the lithium salt composite material 10 of the present embodiment serve as the core of the lithium salt composite material 10, and the metal lithium coating layer 12 constitutes the shell of the lithium salt composite material 10. The lithium salt particles 11 and the metal lithium coating layer 12 form a core-shell structure.

[0080] The lithium salt composite material 10 of the embodiment of the present application uses the metal lithium coating layer 12 as a shell layer. After the lithium salt composite material 10 of the embodiment of the present application is added to the negative electrode sheet as an additive, such as preparing the negative electrode sheet together with the negative electrode active material 21 contained in the negative electrode sheet below, the metal lithium and lithium salt in the metal lithium coating layer 12 can provide lithium ions during the charge and discharge process, play a role in lithium replenishment, and improve the initial efficiency of the battery; and after contacting with the electrolyte, the lithium salt particles can form a local high-concentration electrolyte in the negative electrode active layer, thereby forming a stable and component-rich SEI film, thereby improving the cycle performance of the negative electrode sheet.

[0081] Based on the function of the lithium salt composite material 10 of the embodiment of the present application, the lithium salt composite material 10 of the embodiment of the present application can be used as an additive, such as a lithium supplement additive or an SEI film additive for improving the stability of the SEI film. For example, it can be added to the negative electrode active layer to supplement lithium and improve the stability of the SEI film.

[0082] In some embodiments, the mass ratio of the lithium salt particles 11 and the metallic lithium coating layer 12 can be 0.05:1 to 1:1, further can be 0.1:1 to 1:1, and further can be 0.5:1 to 1:1. In exemplary embodiments, the mass ratio can be 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, and the like, which are typical but non-limiting mass ratios.

[0083] In some embodiments, the particle size of the lithium salt composite material 10 is 50 nm to 100 μm, and in exemplary embodiments, it may be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 μm, etc. This particle size range can effectively disperse in the negative electrode active layer and improve dispersibility.

[0084] By controlling the mass ratio of the metallic lithium coating layer 12 and the lithium salt particles 11 and controlling the particle size of the lithium salt composite material 10, it is possible to enhance the initial efficiency of the battery by the lithium salt composite material 10, improve the stability of the lithium salt concentration in the locally high-concentration electrolyte formed in the negative electrode active layer 20 contained in the negative electrode sheet below and the sustainability of the locally high-concentration electrolyte, and improve the stability and ion conductivity of the SEI film formed in the negative electrode sheet.

[0085] In some embodiments, the particle size D50 of the lithium salt particles 11 can be 10-500 nm, and can further be 50-500 nm, 100-400 nm, etc. In exemplary embodiments, the particle size can be 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc., which are typical but non-limiting particle sizes.

[0086] In an exemplary embodiment, the lithium salt in the lithium salt particles 11 may include lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium hexafluorophosphate (LiPF 6 ), at least one of lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0087] Lithium salts of these types and particle sizes have good solubility and can form a local high-concentration electrolyte in the negative electrode active layer 20 contained in the negative electrode sheet below, thereby improving the stability and ion conductivity of the SEI film in the negative electrode sheet below.

[0088] Preparation method of lithium salt composite material

[0089] In the second aspect, the present application embodiment provides a method for preparing the lithium salt composite material 10 of the above application embodiment. Figure 1 As shown, the preparation method of the lithium salt composite material 10 of the embodiment of the present application includes the following steps:

[0090] S01: using a dry method to form a metal lithium coating layer 12 on the surface of a lithium salt particle 11 using a metal lithium raw material to coat the lithium salt particle 11 .

[0091] The dry method in the preparation method of the lithium salt composite material 10 of the present application is relative to the solvent, which means that the metal lithium raw material forms a metal lithium coating layer 12 on the surface of the lithium salt particles 11 under non-solvent conditions. In addition, the coating includes partial coating and full coating.

[0092] Therefore, the method for preparing the lithium salt composite material 10 in the embodiment of the present application directly forms a coating layer on the surface of the lithium salt particles 11 with the metallic lithium raw material, thereby preparing the lithium salt composite material 10 and giving the lithium salt composite material 10 the core-shell structure and function of the lithium salt composite material 10 in the embodiment of the present application.

[0093] In some embodiments, the method of forming a metal lithium coating layer 12 on the surface of the lithium salt particles 11 by a dry method using a metal lithium raw material in step S01 comprises the following steps:

[0094] The metallic lithium raw material is mixed with the lithium salt particles 11 and then heat treated in a protective atmosphere to melt the metallic lithium raw material and form a metallic lithium coating layer 12 on the lithium salt particles 11;

[0095] Or in some embodiments, the method of forming the metal lithium coating layer 12 on the surface of the lithium salt particles 11 by dry method using the metal lithium raw material in step S01 comprises the following steps:

[0096] The metallic lithium raw material and the lithium salt particles 11 are mixed and then roll-pressed to form a metallic lithium coating layer 12 on the lithium salt particles 11 .

[0097] By heat treatment melting or rolling, the metal lithium raw material is coated on the surface of the lithium salt particles 11, so that the metal lithium coating layer 12 can be uniform and effectively coat the lithium salt particles 11. Among them, the heat treatment conditions should be able to ensure that the metal lithium raw material is melted but stable, such as not oxidized. Rolling treatment utilizes the ductility of the metal lithium raw material, but the rolling pressure should be controlled to ensure that the metal lithium raw material can be rolled and stretched and the stability of the lithium salt particles is ensured.

[0098] In the exemplary embodiment, the metallic lithium raw material and the lithium salt particles 11 can be mixed and processed as follows: Figure 1 As shown in Figure A, the lithium salt particles 11 and the metal lithium raw material are laid to form layers, and the lithium salt particle layers and the metal lithium raw material layers are alternately stacked. In this way, the dispersibility of the metal lithium raw material and the lithium salt particles 11 can be effectively improved, and the uniformity of the metal lithium coating layer 12 can be improved after the above-mentioned heat treatment and rolling treatment.

[0099] In an exemplary embodiment, the metallic lithium raw material may be metallic lithium ingot, metallic lithium powder, metallic lithium foil, or metallic lithium rope.

[0100] Negative plate

[0101] In a third aspect, the present application provides a negative electrode sheet. The negative electrode sheet of the present application comprises a current collector and a negative electrode active layer combined with the current collector, wherein the negative electrode active layer contains the lithium salt composite material 10 of the present application embodiment.

[0102] In this way, the negative electrode sheet of the embodiment of the present application is added with the lithium salt composite material 10 of the embodiment of the present application in the negative electrode active layer. Therefore, the lithium salt composite material 10 can play the role of lithium supplementation and effectively improve the initial efficiency of the battery. After contacting with the electrolyte, the lithium salt particles 11 contained in the lithium salt composite material 10 can form a local high-concentration electrolyte in the negative electrode active layer, thereby forming a stable and component-rich SEI film, thereby improving the cycle performance of the negative electrode sheet, and the ion conductivity of the SEI film is high.

[0103] The inventors found in their research that when the lithium salt composite material 10 of the above application embodiment is doped in the negative electrode active layer, the lithium salt composite material 10 contacts the negative electrode active material contained in the negative electrode active layer. Before the battery formation process, the metal coating layer 12 of the lithium salt composite material 10 in contact with the negative electrode active material will migrate to the negative electrode active material, combine with the surface of the negative electrode active material or embed into the surface layer of the negative electrode active material to form an embedding layer.

[0104] As some embodiments of the present application, Figure 2 In Figures B and C, the negative electrode sheet structure of the embodiment of the present application includes a current collector and a negative electrode active layer 20 combined with the current collector. Among them, the negative electrode active layer 20 contains a lithium salt composite material 10 and a negative electrode active material 21. After the lithium salt composite material 10 contacts the negative electrode active material 21, the metal lithium coating layer 12 migrates to the surface of the negative electrode active material 21. It is combined with the surface of the negative electrode active material 21 or embedded in the surface layer of the negative electrode active material 21, or is combined with the surface of the negative electrode active material 21 and the surface layer of the negative electrode active material 21 at the same time. As the metal lithium coating layer 12 migrates and penetrates to the surface of the negative electrode active material 21, part of the lithium salt particles 11 may be exposed.

[0105] When the lithium metal coating layer 12 contained in the lithium salt composite material 10 of the present invention is at least partially embedded in the surface layer of the negative electrode active material 21, a layer such as Figure 2 The metal lithium intercalation layer 22 is shown in Figures B and C.

[0106] Of course, it is not ruled out that there is a lithium salt composite material 10 in the negative electrode active layer 20 without metal lithium migration. Based on the structure of the lithium salt composite material 10, the metal lithium coating layer 12 can migrate to the surface of the negative electrode active material 21 before the negative electrode sheet is subjected to chemical treatment, which can reduce the thickness of the metal lithium coating layer 12 or make the lithium salt particles 11 exposed in advance before the chemical treatment, thereby increasing the rate of forming a local high-concentration electrolyte in the negative electrode active layer 20 after the negative electrode sheet contacts the electrolyte, thereby accelerating the formation of SEI and improving the stability of SEI; the metal lithium migrated to the surface or surface layer of the negative electrode active material 12 can accelerate the rate of lithium ion release during the charge and discharge process, and improve the first effect of the battery.

[0107] In the embodiment, the lithium salt composite material 10 contained in the negative electrode active layer 20 of the negative electrode sheet can be dispersed between adjacent negative electrode active material 21 particles. When the negative electrode sheet of the embodiment of the present application contacts the electrolyte, the electrode liquid infiltrates into the negative electrode active layer 20 and contacts the lithium salt particles 11. The lithium salt particles 11 will at least partially dissolve in the electrolyte, thereby forming a local high-concentration electrolyte in the negative electrode active layer 20. Among them, when the lithium salt particles 11 are partially dissolved, the remaining residual lithium salt is the residual lithium salt particles 11', such as Figure 2As shown in Figure C. During the charge and discharge process, the local high-concentration electrolyte reacts with the interface of the negative electrode active material 21 and can in situ generate inorganic-rich substances such as Figure 2 The SEI film 23 shown in FIG. C in FIG. Moreover, the metal lithium and the remaining lithium salt particles 11 ′ can timely replenish the lithium salt contained in the local high-concentration electrolyte consumed by the formation of the SEI film 23, maintain the stability of the inorganic concentration in the local high-concentration electrolyte, and thus improve the stability of the SEI film 23.

[0108] Therefore, the negative electrode sheet of the embodiment of the present application can effectively improve the initial efficiency of the battery through the lithium salt composite material 10 contained therein, and the lithium salt particles 11 contained therein are at least partially dissolved after contacting the electrolyte and can form a local high-concentration electrolyte in the negative electrode active layer 20, so that during the charge and discharge process, the SEI film 23 is in situ grown at least on the surface of the negative electrode active material 21, and the stability of the SEI film 23 can be effectively guaranteed. At the same time, since the SEI film 23 is grown in the formation treatment stage, the in-situ grown SEI film 23 is rich in components and has high ionic conductivity compared to the current pre-lithiation electrode.

[0109] Based on the lithium salt composite material 10 contained in the negative electrode sheet of the embodiment of the present application, after the negative electrode sheet is subjected to charge and discharge treatment, the surface of the negative electrode active material 21 contained in the negative electrode sheet of the embodiment of the present application generates in situ inorganic-rich Figure 2 Therefore, in some embodiments, after the negative electrode sheet of the embodiment of the present application is formed (charge and discharge treatment), a SEI film 23 is in-situ grown on at least the surface of the negative electrode active material 21.

[0110] In the exemplary embodiment, the SEI film 23 grown on the surface of the negative electrode active material 21 at least covers the negative electrode active material 21. Figure 2 As shown in Figure C in FIG. Among them, the relatively ideal coating is full coating. Of course, it is not excluded that at least part of the SEI film 23 is half coated.

[0111] Wherein, when the SEI film 23 coated with the negative electrode active material 21 after chemical formation means that the SEI film 23 is coated with Figure 2 The metal lithium intercalation layer 22 in the negative electrode active material 21. When the negative electrode active material 21 has metal lithium bound to its surface, the SEI film 23 covers the negative electrode active material 21 having metal lithium bound to its surface.

[0112] In some embodiments, the mass ratio of the lithium salt composite material 10 to the negative electrode active material 21 can be 0.5:100 to 15:100, and can further be 1:100 to 10:100. In exemplary embodiments, the mass ratio can be 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, etc., which are typical but non-limiting mass ratios.

[0113] By controlling the content of the lithium salt composite material 10 in the negative electrode active layer 20, the effect of the negative electrode sheet on the first effect of the battery can be improved, and the stability of the lithium salt concentration contained in the locally high-concentration electrolyte formed in the negative electrode active layer 20 can be improved, thereby improving the uniformity, stability and ion conductivity of the formed SEI film 23.

[0114] In some embodiments, the particle size D50 of the negative electrode active material 21 in the above embodiments is 3-25 μm, and can further be 5-20 μm, etc. In exemplary examples, it can be 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, etc. Typical but non-limiting particle sizes. The negative electrode active material 21 in this particle size range has a high compaction density.

[0115] In the exemplary embodiment, the negative electrode material in the negative electrode active material 21 includes at least one of graphite, soft carbon, hard carbon, mesophase carbon microspheres, nanocarbon, elemental silicon, silicon-oxygen compounds, silicon-carbon composites, and silicon-tin alloys. These negative electrode materials have high conductivity and high capacity, and they can improve the ability of the negative electrode active material 21 to embed metal lithium, and can improve the stability of metal lithium embedding. For example, when the negative electrode material is graphite, the metal lithium can be embedded between the graphite layers to form a metal lithium embedding layer 22, or combined on the surface of the graphite sheet at the same time.

[0116] In addition, the negative electrode active layer 20 contained in the negative electrode sheet in the above embodiments contains not only the negative electrode active material 21 and the lithium salt composite material 10 mentioned above, but also contains a binder contained in the negative electrode active layer or further contains components such as a conductive agent. The binder can effectively bind the negative electrode active material 21, the lithium salt composite material 10 and the conductive agent and other components to ensure the compaction density, peel strength and other mechanical properties of the negative electrode active layer 20. Among them, if the binder Figure 2 As shown in Figures A, B and C, the binder 03 can effectively bind components such as the negative electrode active material 21, the lithium salt particles 23 and the conductive agent.

[0117] In the embodiment, the mass percentage of the binder 24 in the negative electrode active layer 20 is 0.5-5%, and further can be 2-3%. In the exemplary embodiment, the binder can include but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid, polyimide, and polyacrylonitrile. The binder with this content range and type can enhance the bonding strength between the negative electrode active material 21 and the lithium salt composite material 10, improve the mechanical properties of the negative electrode active layer 20, and improve the energy density and cycle performance of the negative electrode sheet of the embodiment of the present application.

[0118] In the embodiment, when the negative electrode active layer 20 contains a conductive agent, the mass percentage of the conductive agent in the negative electrode active layer 20 may be 0.5-5%, and further may be 2-3%. In the exemplary embodiment, the conductive agent may include but is not limited to at least one of conductive carbon black, superconducting carbon black, conductive graphite, acetylene black, Ketjen black, graphene or carbon nanotubes. The conductive agent of this content range and type can be evenly dispersed, and has a synergistic effect of conductivity with the modified graphite and other components contained in the negative electrode active layer 20, thereby improving the electronic conductivity of the negative electrode active layer.

[0119] Of course, the negative electrode active layer 20 contained in the negative electrode sheet in the above embodiments may also contain corresponding auxiliary components, such as thickeners or dispersants, etc., and the content can be selected and controlled as needed. The presence of these components can improve the dispersion uniformity and performance stability of the components contained in the negative electrode active layer 20.

[0120] Method for preparing negative electrode sheet

[0121] In a third aspect, the present application provides a method for preparing the above negative electrode sheet. The process flow of the negative electrode sheet preparation method of the present application is as follows: Figure 2 As shown, the following steps are included:

[0122] S01: Provide the lithium salt composite material 10 of the above application example;

[0123] S02: preparing a negative electrode slurry by mixing the lithium salt composite material 10 with a negative electrode active material 21;

[0124] S03: coating the negative electrode slurry on at least one surface of the current collector to form a negative electrode active layer 20 to obtain a negative electrode sheet.

[0125] The preparation method of the negative electrode sheet of the embodiment of the present application prepares the lithium salt composite material 10 of the embodiment of the present application together with the negative electrode slurry components including the negative electrode active material 21 and other components into a negative electrode slurry. After the negative electrode active layer 20 is formed on the current collector, the lithium salt composite material 10 can be fully mixed with the negative electrode active material, so that the lithium salt composite material 10 can fully play the role of lithium supplementation during the charge and discharge process and the lithium salt can form a local high-concentration electrolyte in the negative electrode active layer 20, thereby forming a stable and component-rich SEI film, thereby improving the cycle performance of the negative electrode sheet.

[0126] When the prepared negative electrode sheet is in a static state before being used in the formation treatment of the battery, the metal lithium coating layer 12 contained in the lithium salt composite material 10 contacts the negative electrode active material 21, and the metal lithium in the metal lithium coating layer 12 migrates to the surface of the negative electrode active material 21, as described in the negative electrode sheet above, at least combined with the surface of the negative electrode active material 21 or embedded in the surface layer of the negative electrode active material 21, or at least combined with the surface of the negative electrode active material 21 and embedded in the surface layer of the negative electrode active material 21 at the same time. As the metal lithium in the metal lithium coating layer 12 gradually combines with the surface of the negative electrode active material 21 or embeds into the surface layer of the negative electrode active material 21, at least part of the lithium salt particles 11 may be gradually exposed. Among them, the metal lithium embedded in the surface layer of the negative electrode active material 21 forms the metal lithium embedding layer 22 contained in the negative electrode sheet of the above text application embodiment on the surface layer of the negative electrode active material 21.

[0127] Therefore, in some embodiments, the negative electrode sheet preparation method of the present application embodiment can effectively dope the lithium salt composite material 10 into the negative electrode active layer 20, and make the metal lithium contained in the lithium salt composite material 10 at least bonded to the surface of the negative electrode active material 21 or embedded in the surface layer of the negative electrode active material 21, so that the lithium salt particles 11 are exposed and dispersed in the negative electrode active layer 20, so that the negative electrode sheet of the present application can at least grow the SEI film 23 in situ on the surface of the negative electrode active material 21 during the formation process, and effectively ensure the stability of the SEI film 23, and the SEI film 23 is rich in components and has high ion conductivity. In addition, the negative electrode sheet preparation method of the present application embodiment can ensure that the structure and electrochemical performance of the prepared negative electrode sheet are stable, and the efficiency is high, saving production costs.

[0128] Step S01:

[0129] Since the lithium salt composite material 10 in step S01 is the lithium salt composite material 10 in the embodiment of the above application, in order to save the space of this specification, the lithium salt composite material 10 will not be described in detail here.

[0130] Step S02:

[0131] In preparing the negative electrode slurry, in some embodiments, the lithium salt composite material 10 and the negative electrode active material 21 can be mixed in a mass ratio of 0.5:100 to 15:100, and can further be 1:100 to 10:100. In the exemplary embodiment, the mass ratio can be 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, etc., which are typical but non-limiting mass ratios. This ensures that the mass ratio between the lithium salt composite material 10 and the negative electrode active material 21 in the active layer 02 contained in the prepared negative electrode sheet can be within the ratio range of the lithium salt composite material 10 and the negative electrode active material 21 contained in the negative electrode sheet of the above-mentioned application embodiment.

[0132] In addition, the prepared negative electrode slurry may also contain a binder or further contain components such as a conductive agent.

[0133] In an exemplary embodiment, the types of the binder and the conductive agent may be the types of the binder and the conductive agent contained in the negative electrode active layer 20 of the negative electrode sheet of the embodiment of the present application.

[0134] Of course, in order to improve the uniformity and stability of the negative electrode slurry, other additives such as dispersants, thickeners and other components may be added to the negative electrode slurry.

[0135] Step S03:

[0136] The method of forming a negative electrode active layer 20 by coating the negative electrode slurry on the current collector may include coating the negative electrode slurry, drying the negative electrode slurry, and then performing processes such as rolling and cutting, so that the formed negative electrode active layer 20 meets the quality requirements of the negative electrode sheet, such as having high compaction density and mechanical properties.

[0137] Battery

[0138] In a fourth aspect, an embodiment of the present application provides a battery, which includes a negative electrode sheet, and the negative electrode sheet is the negative electrode sheet of the embodiment of the above text application.

[0139] In an exemplary embodiment, the battery of the present application embodiment may be a secondary battery. When the battery of the present application embodiment is a secondary battery, it includes a positive electrode, a separator and a negative electrode sheet. That is, the negative electrode sheet contained in the secondary battery is the negative electrode sheet of the above-mentioned embodiment of the present application.

[0140] In this way, the battery of the embodiment of the present application, such as a secondary battery, has good cycle stability, and high first efficiency and energy density.

[0141] In an embodiment, the secondary battery of the present application may include any one of a battery cell, a battery module, and a battery pack.

[0142] The battery cell refers to a battery housing and a battery cell encapsulated in the battery housing. The shape of the battery cell is not particularly limited and can be cylindrical, square or any other shape. Figure 3 The battery cell 30 shown has a square structure.

[0143] In some embodiments, Figure 4 As shown, the outer packaging of the battery cell 30 may include a shell 31 and a cover plate 33. The shell 31 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 31 has an opening connected to the receiving cavity, and the cover plate 33 is used to cover the opening to close the receiving cavity. The positive electrode, separator and negative electrode sheet contained in the secondary battery of the embodiment of the present application can form an electrode assembly 32 through a winding process and / or a lamination process. The electrode assembly 32 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 32. The number of electrode assemblies 32 contained in the battery cell 30 may be one or more, which can be adjusted according to actual needs.

[0144] The preparation method of the battery cell 30 is well known. In some embodiments, the positive electrode, the separator, the negative electrode sheet and the electrolyte can be assembled to form the battery cell 30. As an example, the positive electrode, the separator and the negative electrode sheet can be formed into an electrode assembly 32 through a winding process or a lamination process, and the electrode assembly 32 is placed in an outer package, dried and injected with electrolyte, and then vacuum packaged, left to stand, formed, shaped and other processes are performed to obtain the battery cell 30.

[0145] The battery module is assembled from the battery cells 30 , that is, it may contain a plurality of the battery cells 30 , and the specific number can be adjusted according to the application and capacity of the battery module.

[0146] In some embodiments, Figure 5 FIG. 4 is a schematic diagram of a battery module 40 as an example. Figure 5 As shown, in the battery module 40, the plurality of battery cells 30 may be arranged in sequence along the length direction of the battery module 40. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 30 may be fixed by fasteners.

[0147] Optionally, the battery module 40 may further include a housing having an accommodation space, and the plurality of battery cells 30 may be accommodated in the accommodation space.

[0148] A battery pack is composed of the above-mentioned battery cells 30, that is, it may contain multiple battery cells 30, wherein multiple battery cells 30 may be assembled into the above-mentioned battery module 40. The specific number of battery cells 30 or battery modules 40 contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0149] As in the embodiment, Figure 6 and Figure 7 is a schematic diagram of an example battery pack 50. The battery pack 50 may include a battery box and a plurality of battery modules 40 disposed in the battery box. The battery box includes an upper box body 51 and a lower box body 52, wherein the upper box body 51 is used to cover the lower box body 52 and form a closed space for accommodating the battery modules 40. The plurality of battery modules 40 may be arranged in the battery box in any manner.

[0150] Electrical devices

[0151] In a sixth aspect, the present application also provides an electric device, which includes the secondary battery of the above-mentioned application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. Therefore, the electric device of the present application has a long standby or battery life.

[0152] The electrical device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc. The electrical device may select a secondary battery, a battery module or a battery pack according to its use requirements.

[0153] Figure 8 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0154] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0155] Example

[0156] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0157] 1. Lithium salt composite material and preparation method thereof

[0158] Example A1

[0159] This embodiment provides a lithium salt composite material and a preparation method thereof, including a lithium salt LiPF 6Particles and coated with LiPF 6 The metal lithium coating of the particles has a structure such as Figure 1 As shown in Figure B. Among them, the lithium salt LiPF 6 The particle size is 25nm, and the lithium salt LiPF 6 The mass ratio of the particles to the metal lithium coating layer is 0.05:1.

[0160] The preparation method of the lithium salt composite material comprises the following steps:

[0161] LiPF 6 The particles are laid in layers and alternately stacked with lithium foil according to the mass ratio, and then rolled under a pressure of 1 MPa in a protective atmosphere so that the lithium foil is on the LiPF 6 A metal lithium coating layer is formed on the surface of the particles, and then granulation is performed by a stirring method to obtain a lithium salt composite material.

[0162] Example A2

[0163] This embodiment provides a lithium salt composite material and a preparation method thereof, comprising LiFSI particles and a metal lithium coating layer coated on the LiFSI particles, wherein the particle size of the LiFSI particles is 50 nm, and the mass ratio of LiFSI to the metal lithium coating layer is 0.1:1.

[0164] The preparation method of the lithium salt composite material comprises the following steps:

[0165] The LiFSI particles are laid out in layers and alternately stacked with lithium foil in a mass ratio, and then rolled in a protective atmosphere at a pressure of 0.5 MPa to form a metallic lithium coating layer on the surface of the LiFSI particles. The particles are then granulated by stirring to obtain a lithium salt composite material.

[0166] Example A3

[0167] This embodiment provides a lithium salt composite material and a preparation method thereof, comprising LiDFOB particles and a metal lithium coating layer coated on the LiDFOB particles, wherein the particle size of the LiDFOB particles is 80 nm, and the mass ratio of the LiDFOB particles to the metal lithium coating layer is 0.2:1.

[0168] The preparation method of the lithium salt composite material comprises the following steps:

[0169] LiDFOB particles are laid out in layers and alternately stacked with lithium foil in a mass ratio, and then rolled in a protective atmosphere at a pressure of 3MPa to form a metallic lithium coating layer on the surface of the LiDFOB particles. The particles are then granulated by stirring to obtain a lithium salt composite material.

[0170] Example A4

[0171] This embodiment provides a lithium salt composite material and a preparation method thereof, comprising LiTFSI particles and a metal lithium coating layer coated on the LiTFSI particles, wherein the particle size of the LiTFSI particles is 12 nm, and the mass ratio of the LiTFSI particles to the metal lithium coating layer is 0.1:1.

[0172] The preparation method of the lithium salt composite material comprises the following steps:

[0173] The LiTFSI particles are laid out in layers and alternately stacked with lithium foils according to a mass ratio, and then rolled in a protective atmosphere at a pressure of 0.5 MPa to form a metallic lithium coating layer on the surface of the LiTFSI particles. The particles are then granulated by stirring to obtain a lithium salt composite material.

[0174] Example A5

[0175] This embodiment provides a lithium salt composite material and a preparation method thereof, comprising LiTFSI particles and a metal lithium coating layer coated on the LiTFSI particles, wherein the particle size of the LiTFSI particles is 20 nm, and the mass ratio of the LiTFSI particles to the metal lithium coating layer is 1:1.

[0176] The preparation method of the lithium salt composite material comprises the following steps:

[0177] The LiTFSI particles and lithium powder are mixed, and then the mixture is heat-treated at 200° C. in a protective atmosphere to melt the lithium powder on the surface of the LiTFSI particles to form a metal lithium coating layer, and then granulated by stirring to obtain a lithium salt composite material.

[0178] Example A6

[0179] This embodiment provides a lithium salt composite material and a preparation method thereof, comprising lithium salt lithium difluorophosphate particles and a metal lithium coating layer coated on the lithium difluorophosphate particles, the structure of which is as follows: Figure 1 As shown in Figure B, the particle size of the lithium salt lithium difluorophosphate particles is 100 nm, and the mass ratio of the lithium salt lithium difluorophosphate particles to the metal lithium coating layer is 0.1:1.

[0180] The preparation method of the lithium salt composite material comprises the following steps:

[0181] The lithium difluorophosphate particles are laid out in layers and alternately stacked with lithium foil in a mass ratio, and then rolled in a protective atmosphere at a pressure of 1.5 MPa to form a metallic lithium coating layer on the surface of the lithium difluorophosphate particles. The particles are then granulated by stirring to obtain a lithium salt composite material.

[0182] 2. Negative electrode sheet and preparation method thereof

[0183] Example B1

[0184] This embodiment provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet includes a copper foil current collector and a negative electrode active layer bonded to the copper foil current collector. The negative electrode active layer contains metallic lithium, lithium salt particles, and negative electrode active materials, the lithium salt particles and the negative electrode active materials are dispersed in the negative electrode active layer, and at least part of the metallic lithium is embedded in the surface layer of the negative electrode active material, such as Figure 2 The structure shown in Figure B. After the negative electrode sheet is formed in the following battery, an SEI film is formed on the surface of the negative electrode active material, such as Figure 2 As shown in Figure C in the figure. The metal lithium and lithium salt contained in the negative electrode active layer are provided by the lithium salt composite material in the above-mentioned embodiment A1. Before the formation of the negative electrode sheet, the total mass ratio of the metal lithium and lithium salt particles contained therein to the mass ratio of the negative electrode active material is 1:20; the negative electrode material is graphite powder with a particle size of 10 μm.

[0185] The method for preparing the negative electrode sheet of this embodiment includes the following steps:

[0186] Graphite powder, polytetrafluoroethylene, conductive carbon black and the salt composite material in Example A1 are mixed and stirred, and the resulting mixture is formed into a film on a current collector and roll-formed, and allowed to stand for 72 hours, so that the salt composite material is unfortunately metallic lithium embedded in the graphite to obtain a negative electrode sheet.

[0187] Example B2

[0188] This embodiment provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet is different from the embodiment B1 in that the metal lithium and lithium salt contained in the negative electrode active layer are provided by the lithium salt composite material in the above embodiment A2. Among them, before the formation of the negative electrode sheet, the total mass ratio of the metal lithium and lithium salt particles contained in the negative electrode sheet to the mass ratio of the negative electrode active material is 1:50; the negative electrode material is soft carbon with a particle size of 20 μm.

[0189] The method for preparing the negative electrode sheet of this embodiment includes the following steps:

[0190] The soft carbon, polytetrafluoroethylene, conductive carbon black and the salt composite material in Example A2 are mixed and stirred, and the resulting mixture is formed into a film on a current collector and roll-formed, and allowed to stand for 48 hours, so that the salt composite material is unfortunately combined with metallic lithium on the surface of the soft carbon or further embedded in the soft carbon to obtain a negative electrode sheet.

[0191] Example B3

[0192] This embodiment provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet is different from the embodiment B1 in that the metal lithium and lithium salt contained in the negative electrode active layer are provided by the lithium salt composite material in the above embodiment A3. Among them, before the formation of the negative electrode sheet, the total mass ratio of the metal lithium and lithium salt particles contained in the negative electrode sheet to the mass ratio of the negative electrode active material is 1:10; the negative electrode material is a graphite powder with a particle size of 5μm.

[0193] The method for preparing the negative electrode sheet of this embodiment includes the following steps:

[0194] Graphite powder, polytetrafluoroethylene, acetylene black and the salt composite material in Example A3 are mixed and stirred, and the resulting mixture is formed into a film on a current collector and roll-formed, and allowed to stand for 48 hours, so that the salt composite material is unfortunately combined with metallic lithium on the soft carbon surface or further embedded in the soft carbon to obtain a negative electrode sheet.

[0195] Example B4

[0196] This embodiment provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet is different from the embodiment B1 in that the metal lithium and lithium salt contained in the negative electrode active layer are provided by the lithium salt composite material in the above embodiment A4. Among them, before the formation of the negative electrode sheet, the total mass ratio of the metal lithium and lithium salt particles contained in the negative electrode sheet to the mass ratio of the negative electrode active material is 1:100; the negative electrode material is hard carbon with a particle size of 25μm.

[0197] The method for preparing the negative electrode sheet of this embodiment includes the following steps:

[0198] The hard carbon, polytetrafluoroethylene and graphene and the salt composite material in Example A4 are mixed and stirred, and the resulting mixture is formed into a film on a current collector and roll-formed, and allowed to stand for 50 hours, so that the salt composite material is unfortunately combined with metallic lithium on the surface of the soft carbon or further embedded in the soft carbon to obtain a negative electrode sheet.

[0199] Example B5

[0200] This embodiment provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet is different from the embodiment B1 in that the metal lithium and lithium salt contained in the negative electrode active layer are provided by the lithium salt composite material in the above embodiment A5. Among them, before the formation of the negative electrode sheet, the total mass ratio of the metal lithium and lithium salt particles contained in the negative electrode sheet to the mass ratio of the negative electrode active material is 1:10; the negative electrode material is hard carbon with a particle size of 3μm.

[0201] The method for preparing the negative electrode sheet of this embodiment includes the following steps:

[0202] The hard carbon, polytetrafluoroethylene and graphene and the salt composite material in Example A5 are mixed and stirred, and the resulting mixture is formed into a film on a current collector and roll-formed, and allowed to stand for 48 hours, so that the salt composite material is unfortunately combined with metallic lithium on the surface of the soft carbon or further embedded in the soft carbon to obtain a negative electrode sheet.

[0203] Example B6

[0204] This embodiment provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet is different from the embodiment B1 in that the metal lithium and lithium salt contained in the negative electrode active layer are provided by the lithium salt composite material in the above embodiment A6. Among them, before the formation of the negative electrode sheet, the total mass ratio of the metal lithium and lithium salt particles contained in the negative electrode sheet to the mass ratio of the negative electrode active material is 1:30; the negative electrode material is hard carbon with a particle size of 15μm.

[0205] The method for preparing the negative electrode sheet of this embodiment includes the following steps:

[0206] The hard carbon, polytetrafluoroethylene and graphene and the salt composite material in Example A6 are mixed and stirred, and the resulting mixture is formed into a film on a current collector and roll-formed, and allowed to stand for 48 hours, so that the salt composite material is unfortunately combined with metallic lithium on the surface of the soft carbon or further embedded in the soft carbon to obtain a negative electrode sheet.

[0207] Comparative Example B1

[0208] This comparative example provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet of this comparative example is different from the negative electrode sheet in Example B1 in that it does not contain lithium salt particles and metallic lithium.

[0209] The preparation method thereof is different from that of the negative electrode sheet in Example B1 in that graphite powder, polytetrafluoroethylene and conductive carbon black are directly mixed and stirred to prepare the negative electrode sheet.

[0210] Comparative Example B2

[0211] This comparative example provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet of this comparative example is different from the negative electrode sheet in Example B2 in that it does not contain lithium salt particles and metallic lithium.

[0212] The preparation method thereof is different from that of the negative electrode sheet in Example B2 in that soft carbon, polytetrafluoroethylene and conductive carbon black are directly mixed and stirred to prepare the negative electrode sheet.

[0213] Comparative Example B3

[0214] This comparative example provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet of this comparative example is different from the negative electrode sheet in Example B3 in that it does not contain lithium salt particles and metallic lithium.

[0215] The preparation method thereof is different from that of the negative electrode sheet in Example B3 in that graphite powder, polytetrafluoroethylene and acetylene black are directly mixed and stirred to prepare the negative electrode sheet.

[0216] Comparative Example B4

[0217] This comparative example provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet of this comparative example is different from the negative electrode sheet in Example B4 in that it does not contain lithium salt particles and metallic lithium.

[0218] Its preparation method is different from that of the negative electrode sheet in Example B4 in that hard carbon, polytetrafluoroethylene and graphene are directly mixed and stirred to prepare the negative electrode sheet.

[0219] 2. Secondary battery example

[0220] Example C1 to Example C6 and Comparative Example C1 to Comparative Example C4

[0221] Embodiments C1 to C6 and Comparative Examples B1 to B4 provide a secondary battery respectively. Each secondary battery includes a battery cell formed by a positive electrode sheet, a separator and a negative electrode sheet, and also includes an electrolyte.

[0222] The positive electrode sheet is prepared according to the following method:

[0223] Embodiments B1 to B2 use lithium iron phosphate positive electrode, and the preparation method is that lithium iron phosphate, PVDF and conductive carbon are mixed in a ratio of 8:1:1, N-methyl pyrrolidone is added, stirred, coated and dried; Embodiments B3 to B4 use ternary positive electrode NCM523, and the preparation method is that ternary material NCM523, PVDF and conductive carbon are mixed in a ratio of 8:1:1, N-methyl pyrrolidone is added, stirred, coated and dried; Embodiments B5 to B6 use ternary positive electrode NCM622, and the preparation method is that ternary material NCM622, PVDF and conductive carbon are mixed in a ratio of 8:1:1, N-methyl pyrrolidone is added, stirred, coated and dried;

[0224] Negative electrode sheet: the negative electrode sheet provided in the above Examples B1 to B6 and Comparative Examples B1 to B5 respectively;

[0225] Electrolyte: The electrolyte used in Examples B1 to B2 is: 2% LiNO 3 , 1M LiTFSI DOL / DME (volume ratio 1:1); the electrolyte used in Example B3 to Example B4 is: 2% FEC, 1M LiPF6 EC / DEC (volume ratio 3:7); the electrolyte used in Example B3 to Example B6 is: 2% VC, 1M LiPF6 EC / DMC (volume ratio 3:7).

[0226] Separator: The separators of Examples B1 and B2 use polyethylene separators, Examples B3 and B4 use polypropylene separators, and Examples B5 and B6 use polyacrylonitrile separators.

[0227] Secondary battery assembly: stack the positive electrode sheet / diaphragm / negative electrode sheet in the order of stacking to form a battery cell, place the bare battery cell in an outer package, inject the above-mentioned electrolyte and seal it to obtain secondary batteries respectively; wherein, the secondary battery in Example C1 contains the negative electrode sheet provided in Example B1 above, the secondary battery in Example C2 contains the negative electrode sheet provided in Example B2 above, and so on, the secondary battery in Comparative Example C1 contains the negative electrode sheet provided in Comparative Example B1 above.

[0228] Secondary battery related data test

[0229] After the secondary battery monomers in the above-mentioned embodiments and comparative examples were subjected to formation treatment, the SEI films contained in the negative electrodes were analyzed by X-ray photoelectron spectroscopy to analyze the components contained in each SEI film.

[0230] At the same time, each secondary battery cell after the formation treatment is tested for the relevant items shown in Table 1 below.

[0231] Formation treatment: 0.04C charging to 30% remaining capacity (SOC);

[0232] First effect: C1-C2: 0.33C charge to 4.0V, 0.33C discharge to 2.0V, first effect = discharge capacity / charge capacity;

[0233] C3-C6: 0.33C charge to 4.3V, 0.33C discharge to 2.8V, first effect = discharge capacity / charge capacity;

[0234] Cycle test: C1-C2: 0.33C charge to 4.0V, 0.33C discharge to 2.0V;

[0235] C3-C6: 0.33C charge to 4.3V, 0.33C discharge to 2.8V.

[0236] Test results:

[0237] 1. Test results of SEI film components contained in each negative electrode:

[0238] After formation, the SEI film contained in each negative electrode is rich in components, including LiF, Li 2 O. Li 3 N, ROLi, Li 2 CO 3 And other components. Among them,

[0239] The SEI film contained in the negative electrode sheet of Example B1 after chemical formation contains 33 wt% LiF, 23 wt% Li 2 O, 5wt% Li 3 N, 13wt% ROLi, 26wt% Li 2 CO3 ; Wherein, R in ROLi is an organic group, such as an alkyl group, which can be methyl, ethyl, propyl, isopropyl, etc. The SEI film contained in the negative electrode sheet of Comparative Example B1 after chemical formation contains 13wt% LiF, 25wt% Li 2 O, 7 wt% Li 3 N, 23wt% ROLi, 32wt% Li 2 CO 3 Therefore, the LiF content in the SEI film of the negative electrode sheet in Example B1 after formation is 20% higher than the LiF content in the SEI film of the negative electrode sheet in Comparative Example B1;

[0240] The LiF and Li in the SEI film of the negative electrode sheet of Example B2 after formation 3 The N content is higher than that of LiF and Li in the SEI film of the negative electrode sheet in comparative example B2. 3 N content 40% and 25%;

[0241] The LiF content in the SEI film of the negative electrode sheet in Example B3 after formation is 30% higher than the LiF content in the SEI film of the negative electrode sheet in Comparative Example B3;

[0242] The LiF and Li in the SEI film of the negative electrode sheet of Example B4 after formation 3 The N content is higher than that of LiF and Li in the SEI film of the negative electrode sheet in comparative example B4. 3 N content 25% and 12%.

[0243] It can be seen from the SEI film components that the negative electrode sheet of the embodiment of the present application is prepared by adding the lithium salt composite material of the embodiment of the present application to the negative electrode slurry so that the lithium salt composite material reacts with the negative electrode material, thereby

[0244] 2. Test results of secondary battery monomer related items:

[0245] Table 1

[0246] Example First effect Cycle life (number of turns) Example C1 93% 2000 Comparative Example C1 87% 1000 Example C2 95% 1100 Comparative Example C2 89% 450 Example C3 92% 1000 Comparative Example C3 85% 500 Example C4 95% 1000 Comparative Example C4 88% 500

[0247] As can be seen from Table 1, the first effect and cycle performance of the secondary battery of the embodiment of the present application are significantly better than the first effect and cycle performance of the secondary battery in each comparative example. Therefore, after the negative electrode sheet of the embodiment of the present application is added with the lithium salt composite material of the embodiment of the present application to the active layer of the negative electrode sheet, the first effect and cycle performance of the negative electrode sheet are significantly improved. It can be seen that after the lithium salt composite material of the embodiment of the present application is added to the negative electrode active layer of the negative electrode sheet as a negative electrode additive, it can effectively play a role in replenishing lithium; and it can grow an SEI film at least on the surface of the negative electrode active material, and the SEI film components are rich, and the SEI film has high stability, thereby effectively improving the first effect and cycle performance of the battery.

[0248] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A lithium salt composite material, characterized in that: comprising lithium salt particles and a metal lithium coating layer coating the lithium salt particles; The mass ratio of the lithium salt particles to the metal lithium coating layer is 0.05:1 to 1:1; The average particle size Dv50 of the lithium salt composite material is 50nm-100μm.

2. The lithium salt composite material according to claim 1, characterized in that: The lithium salt in the lithium salt particles comprises at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide); and / or The average particle size Dv50 of the lithium salt particles is 10 to 500 nm.

3. A method for preparing the lithium salt composite material according to claim 1 or 2, characterized in that: The steps include: A metallic lithium raw material is used in a dry method to form a metallic lithium coating layer on the surface of lithium salt particles to coat the lithium salt particles.

4. The preparation method according to claim 3, characterized in that: The method of using a metallic lithium raw material to form a metallic lithium coating layer on the surface of lithium salt particles by a dry method comprises the following steps: The metallic lithium raw material and the lithium salt particles are mixed and then heat treated in a protective atmosphere to melt the metallic lithium raw material and form the metallic lithium coating layer on the surface of the lithium salt particles; or The metal lithium raw material and the lithium salt particles are mixed and then subjected to a roll pressing process, so that the metal lithium raw material forms the metal lithium coating layer on the surface of the lithium salt particles.

5. A negative electrode sheet, comprising a current collector and a negative electrode active layer combined with the current collector, characterized in that: The negative electrode active layer contains the lithium salt composite material according to claim 1 or 2 and the lithium salt composite material prepared by the preparation method according to claim 3 or 4, and the negative electrode active layer also contains a negative electrode active material.

6. The negative electrode sheet according to claim 5, characterized in that: The mass ratio of the lithium salt composite material to the negative electrode active material is 0.5:100 to 15:

100.

7. The negative electrode sheet according to claim 5 or 6, characterized in that: The metal lithium in the metal lithium coating layer contained in the lithium salt composite material is at least partially combined with the surface of the negative electrode active material or / and embedded in the surface layer of the negative electrode active material.

8. The negative electrode sheet according to claim 5 or 6, characterized in that: The negative electrode active material comprises at least one of graphite, soft carbon, hard carbon, mesophase carbon microspheres, nanocarbon, elemental silicon, silicon-oxygen compounds, silicon-carbon composites, and silicon-tin alloys; and / or The average particle size Dv50 of the negative electrode active material is 3 to 25 μm.

9. A method for preparing a negative electrode sheet, characterized in that: The steps include: Providing a lithium salt composite material; the lithium salt composite material is the lithium salt composite material according to claim 1 or 2 or the lithium salt composite material prepared by the preparation method according to claim 3 or 4; The lithium salt composite material and negative electrode active materials are prepared into negative electrode slurry; The negative electrode slurry is coated on at least one surface of a current collector to obtain a negative electrode sheet.

10. The preparation method according to claim 9, characterized in that: The lithium salt composite material and the negative electrode active material are mixed in a mass ratio of 0.5:100 to 15:

100.

11. A battery, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 5 to 8 or the negative electrode sheet prepared by the preparation method according to claim 9 or 10.

12. The battery according to claim 11, characterized in that: After the battery is subjected to formation treatment, the negative electrode active layer contains exposed lithium salt particles; and / or After the battery is subjected to formation treatment, a solid electrolyte interface film is formed on the surface of the negative electrode active material contained in the negative electrode sheet, and the solid electrolyte interface film at least partially covers the negative electrode active material.

13. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 11 or 12, and the battery is used to provide electrical energy.

Citation Information

Patent Citations

  • Anode material and anode and battery provided with anode and preparation method of anode material

    CN103165885A

  • Negative electrode additive, secondary battery, battery module, battery pack and device

    CN112563463A